Improving equity through barrier-free transportation: an evaluation of Shanghai metro stations - Zhang, Zhan; Yang, Xiongjie; Jiang, Chenming; Lu, Linjun; Li, Xiaoyue; Rong, Xiaoyu; Huang, Ziqi (Frontiers in Public Health, 2025)
IntroductionAs urbanization progresses and vulnerable populations increase, equitable accessibility remains a critical issue. This study evaluates the accessibility of transit-oriented development (TOD) in Shanghai, focusing on barrier-free facilities in metro stations.MethodsA comprehensive evaluation framework combining the Analytic Hierarchy Process (AHP) and the System Usability Scale (SUS) was developed to assess metro station accessibility. Thirteen evaluation factors formed a composite accessibility index. A case study of two Shanghai metro stations, Xinzhuang and Xujiahui, was conducted using quantitative metrics, surveys, and interviews.ResultsA strong correlation between AHP scores and SUS ratings validated the framework’s reliability. The study provides recommendations for enhancing metro accessibility.DiscussionThe proposed framework offers a robust tool for evaluating and improving urban transit accessibility, with implications for inclusive mobility policy and design.